ENSURING THE LEVEL OF ENVIRONMENTAL SAFETY OF PROCESSES WHEN PROCESSING ELECTRONIC AND ELECTRICAL WASTE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article discusses such issues as the recycling of electrical and electronic waste (EEW), modern methods and technologies of disposal with the condition of strict adherence to a number of requirements that ensure the environmental safety of all technological processes. It highlights the sources of education, the composition, the volume of EEW accumulated around the world and the adopted legislative and legal acts, including the first published Directives in developed countries such as the USA, Japan, the European Union, and the countries of the BRICS organization.